Analisis Implementasi Penyaluran Dana Zis Di Bmt Bina Dhuafa Bringharjo - Santoso, Ivan Rahmat (Jurnal Akuntansi, 2014)
The Distribution Of Zakat, Donation, And Alms From Muslims As Early As Possible Should Be Channeled Effectivity As An Economic Empowerment Initiative Of The People